Developing Adaptive Multi Dimension Road Construction Management Using EDAS Technique - Nazar Jabbar, Ayat; Naimi, Sepanta (International Journal of Sustainable Construction Engineering and Technology, 2023)
Adaptive road construction project Management is considered a major challenge in economic development issues. This research looks into the many variables that can have an impact on building projects. Unfortunately, infrastructure projects in Iraq have slowed the country's progress, so effective methods of project management using actual databases are urgently needed. This research established a centralized data bank with a collection of specialized maps depicting the status of infrastructure projects in Iraq, and it also produced an advanced administrative system via effective success and failure elements that allow administration of projects. Implementing adaptive features during road construction projects is the primary problem of this study. There were two stages to the study methodology; the first was the Delphi technique, which was used to determine the first set of influential elements. The EDAS method was employed in the second approach, and it provided the most useful information regarding the aspects that could affect road construction projects positively or negatively. According to the findings, there were a number of effective factors that could lead to the failure of road construction projects. These included insufficient site security, poor site management and supervision, ineffective field management, inexperienced equipment operators, and insufficient consultant experience. The findings may be helpful for the policy makers and the practitioners in future.